Production components of agroindustrial interest of sugarcane varieties under subsurface drip irrigation in semiarid conditions - Simões, Welson Lima; de Oliveira, Cíntia Patrícia Martins [UNESP]; de Oliveira, Anderson Ramos; Faria, Glaucia Amorim [UNESP]; Guimarães, Miguel Júlio Machado; Tardin, Flávio Dessaune; Silva, Jucicléia Soares da (Universidade Estadual de Maringa, 2023)
The identification of promising commercial varieties for irrigated crops in semiarid conditions based on characters of interest to sugarcane agro-industries is important, considering the search for high sugarcane yields to obtain sustainable crops. Thus, the objective of this work was to evaluate production components of agroindustrial interest of different sugarcane varieties grown under subsurface drip irrigation in the Semiarid region of Brazil, during two crop cycles. A randomized block experimental design was used, in an 8×2 factorial arrangement (varieties and cycles) with three replications. The sugarcane juice quality, sugar yield, and culm yield were evaluated in each cycle. Gross sugar percentage, sugarcane culm yield, juice apparent sucrose content, and juice purity were affected by the crop cycles. Soluble solids content presented strong significant correlation with most variables of agroindustrial interest. The path coefficient analysis showed that juice apparent sucrose content was the explanatory character with higher direct effect on soluble solids and that this variable presented high indirect effects on most explanatory variables. The sugarcane varieties RB72454 and Q124 are recommended for production managements with drip irrigation under semiarid conditions. Soluble solids content can be used as an alternative for direct selection of varieties with higher sugar yields in different cycles.
Keywords: path coefficient analysis; Pearson's correlation; Saccharum sp; technological quality parameters